Edukasi Kesehatan Reproduksi Melalui Program Understanding Your Body, Protecting Your Future pada Santri Pondok Pesantren - Muniroh Muniroh; Fawwaz Amora Sulthan (Jurnal Medika: Medika, 2025)
Reproductive health is an essential factor in maintaining adolescent well-being, particularly for students living in islamic boarding school (pesantren). Limited knowledge of reproductive health may increase vulnerability to risky behaviors and long-term health problems. This community service program aimed to improve students's knowledge of reproductive health through an educational program themed "Understanding Your Body, Protecting Your Future." The program was conducted using interactive lectures, group discussions, and question-and-answer sessions involving 83 participants at Pondok Pesantren Daru Hasbi.  The results showed an increase in participants' understanding of reproductive anatomy and functions, physical and psychological changes during puberty, personal hygiene, and the importance of maintaining reproductive health. The students considered this activity beneficial as it provided practical knowledge while remaining aligned with religious values. Therefore, reproductive health education in the pesantren context can serve as an effective strategy to enhance adolescents' understanding while equipping them to protect their health and future. This activity needs to be carried out continuously and integrated into the learning process in pesantren, with the involvement of teachers, health professionals, and parental support.